2000
DOI: 10.1046/j.1460-9568.2000.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐3 is activated following axotomy of neonatal facial motoneurons and caspase‐3 gene deletion delays axotomy‐induced cell death in rodents

Abstract: In this report, we examined the possible functions of the cell death protease, caspase-3, in the axotomy-induced apoptosis of facial motoneurons in newborn rodents. Using in situ hybridization and Western blot, we found higher levels of caspase-3 mRNA and pro-caspase-3 protein expression in motoneurons of neonatal and 2-week-old rats than adult rats. Following facial motoneuron axotomy, caspase-3 mRNA and protein expression increased in motoneurons of both neonatal and adult rats. However, using an antibody di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…This may be because of the difficulty in detecting a small number of apoptotic cells over a long time span, because apoptosis is a fast process (Rossiter et al, 1996). A lack of apoptotic cells after adult motor neuron injury has been reported by others (Li et al, 1998;Vanderluit et al, 2000). Adult axotomized rat facial motor neurons may undergo a slow, nonapoptotic form of degeneration (Moran et al, 2001).…”
Section: Long-term Expression Of Truncated Trkb Results In Motor Neurmentioning
confidence: 99%
“…This may be because of the difficulty in detecting a small number of apoptotic cells over a long time span, because apoptosis is a fast process (Rossiter et al, 1996). A lack of apoptotic cells after adult motor neuron injury has been reported by others (Li et al, 1998;Vanderluit et al, 2000). Adult axotomized rat facial motor neurons may undergo a slow, nonapoptotic form of degeneration (Moran et al, 2001).…”
Section: Long-term Expression Of Truncated Trkb Results In Motor Neurmentioning
confidence: 99%
“…Mice were sacrificed 24 h or 4 days following axotomy. For quantitation of survival, every fifth section through the facial nucleus was evaluated by cresyl violet staining and the total number of live motor neurons was evaluated both ispialteral and contralateral to the axotomy as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that this results in apoptotic death, which is associated with caspase induction (33,38). Utilizing this model, we first asked whether JNKs might be required for death.…”
Section: Jnk3 Modulates Death Of Facial Motormentioning
confidence: 99%
“…Experimental animals were backcrossed 4 -10 generations onto the B6 strain and 4 -14 generations onto the 129 strain. Genotyping for the Casp3 wild-type (WT) and knock-out (KO) alleles was performed on DNA from adult tail or ear biopsy or embryo tail, paw, or yolk sac by PCR using the previously described oligonucleotide pairs (Vanderluit et al, 2000). Specifically, the WT Casp3 allele 5Ј primer 5Ј-AAGCTG-TCTTCGTCCAGTGAG-3Ј (oEMS1051) corresponding to base pairs 3122-3142, and the 3Ј primer 5Ј-CTAAGTTAACCAAACTGAGC-ACCGC-3Ј (oEMS905) corresponding to base pairs 3475-3451, generated a band of 353 bp.…”
Section: Methodsmentioning
confidence: 99%